Handling COVID-19: Produce Farms and Packinghouses - Laurel Dunn; Michelle Danyluk (EDIS, 2020)
While there is no evidence that the COVID-19 virus is a food safety concern, it is a worker health concern because it spreads via close person-to-person contact or by contact with contaminated surfaces. Food does not appear to be a likely cause of COVID-19 transmission, but many of the same practices used to prevent foodborne illness on foods should still be used to reduce the likelihood of COVID-19 contamination on fresh produce and the risk of COVID-19 spread among farm and packinghouse workers. This material is adapted from the version published at  https://foodsafety.ces.ncsu.edu/covid-19-resources/. Written by Laurel Dunn and published by the UF/IFAS Food Science and Human Nutrition Department.